HRM Practices in Sugar Cooperatives - A Case Study of Sanjivani Sahakan Sakhar Karkhana Limited, Tiska, Goa - Patil, Sunil Subhash; Patil, V. S. (Prabandhan: Indian Journal of Management, 2010)
From the earlier term ’Employment Management’ evolved the more general term "Personnel Management" which means personnel (human resource), and it refer’s to the employees (staff) working in an organization at different levels. During the later 1960’s and 1970’s, the term ’Manpower Management’ became popular. Now-a-days Human Resource Management (HRM) is widely used. The human resource is the most productive and most versatile.